Global progress in clinical research on human respiratory syncytial virus vaccines - Peng, Ruofan; Chen, Chenghao; Chen, Qian; Zhang, Yuwen; Huang, Renjin; Zhang, Yanjun; Li, Jianhua (Frontiers in Microbiology, 2024)
Human respiratory syncytial virus (hRSV) not only affects newborns but also older adults, contributing to a substantial worldwide burden of disease. However, only three approved hRSV vaccines remain commercially available to date. The development of a safe, practical and broad-spectrum vaccine suitable for all age groups remains extremely challenging. Using five different approaches—live-attenuated, recombinant-vector, subunit, particle-based, and mRNA—nearly 30 hRSV vaccine candidates are currently conducting clinical trials worldwide; moreover, >30 vaccines are under preclinical evaluation. This review presents a comprehensive overview of these hRSV vaccines along with prospects for the development of infectious disease vaccines in the post-COVID-19 pandemic era.